Heat transfer and energy performance analysis of photovoltaic thermal system using functionalized carbon nanotubes enhanced phase change material - Rajamony, Reji Kumar; Pandey, A. K.; Mahendran, Samykano; Johnny Koh, Siaw Paw; Kareri, Tareq; Laghari, Imtiaz Ali; Tyagi, V. V. (Elsevier Ltd, 2024)
The photovoltaic thermal system (PVT) is an emerging technology that simultaneously generates both electrical and thermal energy from solar energy, aiming to improve solar energy utilization. However, significant technological issues with these systems obstruct their large-scale operation. The major drawback of the cooling fluid-based PVT systems lies in operation during sun-shine hours only. To address this issue, the present research endeavors a comparative study on with and without nano-enhanced phase change materials (NePCM) integrated PVT system. In this study, the performance evaluation of four configurations was analyzed with a flow rate varying from 0.4 to 0.8 litter per minute. From this, the experimental analysis was performed on two systems, including a photovoltaic and a PVT system. The simulation was performed using TRNSYS simulation on the phase change materials integrated photovoltaic thermal system, and NePCM integrated photovoltaic thermal system. The results indicates that increasing the flow rate by 2.2 times leads to a 4.9-fold increase in pressure drop, while the friction factor decreases with rising mass flow rate. Notably, the NePCM-integrated PVT system exhibited a substantial reduction in cell temperature and increased electrical power output at higher flow rates. At a flow rate of 0.4litter per minute, a significant heat gain was achieved with an impressive energy-saving efficiency of 75.67 %. Furthermore, the total efficiency of the PVT system, phase change materials integrated PVT system, and NePCM integrated PVT system were determined to be 81.9 %, 84.5 %, and 85.05 %, respectively. These findings underscore the potential of NePCM-integrated PVT systems for enhancing performance and expanding their practical application.